SEARCH FOR EXOTIC PROCESSES AT THE CERN PPBAR COLLIDER - Ansari, R; Bagnaia, P; Banner, M; Battiston, R; Bernlohr, K; Booth, C; Borer, K; Borghini, M; Carboni, G; Cavasinni, V; Cenci, P; Chollet, J; et al. (1987)
The total UA2 data sample at the CERN pp̄ Collider corresponds to an integrated luminosity of 910 nb-1. Limits on various hypothetical processes, such as production of excited electrons, additional charged or neutral vector bosons, or supersymmetric particles, are presented from the analysis of this sample. © 1987.